(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article examines the development of verbal-linguistic intelligence in future educators within the pedagogical process. Drawing on Howard Gardner’s theory of multiple intelligences, it explores methodological approaches, assessment criteria, and practical classroom techniques such as storytelling, linguistic exercises, and expressive writing. Emphasis is placed on fostering communication competence, empathy, and critical thinking skills essential for successful pedagogical engagement.